ENGLISH AS A MEDIUM OF INSTRUCTION: INDONESIAN TERTIARY STUDENTS’ PERCEPTION ON THE STRENGTHS AND WEAKNESSES - Putu Ayu Prabawati Sudana; Ni Made Ratminingsih; Ni Nyoman Padmadewi; Ni Luh Putu Sri Adnyani (SEAQIL Journal of Language Education, 2023)
EMI (English as Medium of Instruction) is an innovative teaching approach where subjects other than English are taught to the students in English, a second or foreign language. This approach has been widely adopted in European and Asian tertiary education institutions, including Indonesia. However, only a limited number of research has been carried out to reveal the student’s perception of the advantages and drawbacks of the implementation in the country. This study, therefore, aimed at investigating the students’ perceptions of the advantages and drawbacks of EMI implementation in one state university in Bali, Indonesia. This study employed mixed-method research, which was carried out with 130 participants enrolled in the international class initiation. The obtained data were collected through questionnaires and interviews. The results of the study showed five significant advantages of EMI class: cognitive advantages, resource availability, rich exposure to English and chances to use it, career opportunity, and improvement of students’ motivation in English. However, EMI students also encountered challenges such as difficulties comprehending lectures/materials, taking tests, and low participation in classroom discussions.